Bacteriophage diversity of Panton-Valentine leukocidine positive clinical Staphylococcus aureus isolates identified in South Africa and Nigeria - Ehlers, Marthie Magdaleen (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2019.